A phase II trial of second-line pemetrexed in adults with advanced/metastatic osteosarcoma - Duffaud, Florence; Egerer, Gerlinde (European journal of cancer, 2012)
Background: Osteosarcoma is the most common primary malignant tumour in young adults. An effective treatment strategy for relapsed patients is still not defined. Pemetrexed is a multitargeted antifolate with a mode of action similar to, and a range of action broader than that of methotrexate. The primary objective of this phase II study was to determine tumour response rate in patients with high-grade, advanced/metastatic osteosarcoma. Secondary end-points included progression-free survival (PFS), overall survival (OS) and safety. Methods: Pemetrexed 500mg/m2 was administered on day 1 of 21-day cycles with folic acid and vitamin B12 supplementation. At least 5 tumour responses in a targeted population of 32 were required to consider further investigation. Results: Thirty-two patients (median age, 43.3years; range, 18.6-76.0) with 1 prior chemotherapy regimen for high-grade advanced/metastatic osteosarcoma were enrolled. Thirty (93.8%) patients had an ECOG performance status ⩽1 and 29 (90.6%) had metastases in the lung. One patient had partial response (3.1%) and 5 (15.6%) had stable disease. Median PFS and OS were 1.4months (95% CI: 1.4-1.7) and 5.5months (95% CI: 2.3-10.5), respectively. The most common drug-related grade 3/4 toxicities were leukopaenia, asthaenia and elevated alanine aminotransferase in 3 (9.4%) patients each. One patient died due to multi-organ failure considered possibly related to the study drug. Conclusions: Pemetrexed 500mg/m2 administered on day 1 of 21-day cycles as second-line treatment to patients with advanced/metastatic high-grade osteosarcoma was generally well tolerated but did not meet minimal response expectations for further investigation in this patient population.